Entre as normas e os desejos : a indexação de periódicos na Biblioteca Central da Uuniversidade Federal da Paraíba - Paiva, Eliane Bezerra (2002)
The amount of information nowadays represents a challenge to every man and creates some barriers to the access of the desired information. The rising of the new technologies of both information and communication increases the offer of information and the possibilities of accessing and disseminating information. Moreover, the lack of financial resources of the Brazilian universities contributes to enlarge the importance of an evaluation of the information services provided by the Information Science. Thus, this present work, supported by the studies of F. W. Lancaster on the information retrieval systems evaluation, focuses on the indexing service of articles from periodicals provided by the Biblioteca Central (BC) of the Universidade Federal da Paraiba (UFPB) and analysis the present conditions of such sector in relation to the users'informational needs, once the indexing consists of a documentary treatment towards a content condensed representation. The articles studied were written in Portuguese and refered to the area of Social Sciences. The relationship between the provided indexing service and the users of such service is analysed here through a methodology that ranges from a documentary research to get information about the implementation of the indexing service and a field research to: a) Evaluate the coverage of the subject catalogue of the periodical setor of Biblioteca Central based on the periodical titles indexed by Rede Bibliodata published by Fundacao Getulio Vargas (FGV); b) Enquiry the indexing service users to check their satisfaction with the service provided. The investigation was structured in two different but complementary steps: a quantitative and a qualitative approaching plans, supported by Bardin's Content Analysis Theory. An enquiry with open and closed questions was applied to collect the data wich after being analysed pointed out to the existence of some relevant collections to the Social Sciences area and to the moderate satisfaction of the users towards the indexing service provided. Nevertheless, this present work shows that it is necessary to improve the indexing service to achieve the users' desidered information reinforcing the assumption that some policies of indexing may guide the setor. Thus, considering the relevant role of the users withing the process of evaluating the indexing service sector towards some decision making, it is suggested here some policies to achieve a balance between the indexing norms and the users'information desires.